2021
DOI: 10.1186/s12916-021-01999-2
|View full text |Cite|
|
Sign up to set email alerts
|

Physician-directed genetic screening to evaluate personal risk for medically actionable disorders: a large multi-center cohort study

Abstract: Background The use of proactive genetic screening for disease prevention and early detection is not yet widespread. Professional practice guidelines from the American College of Medical Genetics and Genomics (ACMG) have encouraged reporting pathogenic variants that confer personal risk for actionable monogenic hereditary disorders, but only as secondary findings from exome or genome sequencing. The Centers for Disease Control and Prevention (CDC) recognizes the potential public health impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Our data on the frequency of verified PLPVs among the ACMG v.2 gene list in biobank participants are consistent with prior population screening efforts using this list that yielded a frequency of such variants of 1%–1.5% among individuals who had been genotyped 53 and 2.6% among individuals who had been sequenced. 54 , 55 , 56 Our data replicate and extend prior observations around the poor performance of GT as a potential tool for biobank gRoR or population screening. 53 , 57 , 58 , 59 Of the initial GT calls from over 36,000 participants from our biobank, nearly 45% of samples initially identified as carrying PLPVs were false positives.…”
Section: Discussionsupporting
confidence: 83%
“…Our data on the frequency of verified PLPVs among the ACMG v.2 gene list in biobank participants are consistent with prior population screening efforts using this list that yielded a frequency of such variants of 1%–1.5% among individuals who had been genotyped 53 and 2.6% among individuals who had been sequenced. 54 , 55 , 56 Our data replicate and extend prior observations around the poor performance of GT as a potential tool for biobank gRoR or population screening. 53 , 57 , 58 , 59 Of the initial GT calls from over 36,000 participants from our biobank, nearly 45% of samples initially identified as carrying PLPVs were false positives.…”
Section: Discussionsupporting
confidence: 83%
“…Initial evidence from population-based genomic screening suggests benefits worthy of its expansion. One study demonstrated a significant finding regarding the implementation of population-based screening [ 29 ]. One laboratory reported that, among 10,478 individuals screened for up to 147 genes, 15.5% had an actionable monogenic disorder identified via the panel, including hereditary cancer and cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Genes for inclusion in these panels were selected based on published guidance from the American College of Medical Genetics and Genomics (ACMG) and ClinGen Working groups, in addition to clinical studies establishing personal risk for monogenic disorders ( Foreman et al, 2013 ; Green et al, 2013 ; Dewey et al, 2016 ; Webber et al, 2018 ). Probands undergoing non-indication-based screening have been described previously ( Haverfield et al, 2021 ). In brief, all probands were included in the analysis, regardless of a personal or family history of cancer or cardiovascular disease.…”
Section: Methodsmentioning
confidence: 99%